Gambaran Pengetahuan Ibu Hamil Tentang Senam Hamil Di Klinik Alisah Medan Periode Maret-Mei 2025 - Adriana Bangun; Putri Diah Pemiliana (STIKES Columbia Asia Medan, 2025)
Prenatal exercise is a program designed specifically for pregnant women, featuring movements tailored to their condition, aimed at reducing discomforts during pregnancy and preparing them both physically and mentally for childbirth. The lack of awareness among pregnant women regarding prenatal exercise is likely a contributing factor to their limited participation. This study aims to explore the level of knowledge pregnant women have about prenatal exercise at Alisah Clinic, Medan, during the period of March to May 2025. The research employed primary data collection using a total sampling technique, with questionnaires as the instrument, involving 30 pregnant women as subjects. Data analysis was conducted using frequency distribution in percentages. The results showed that the majority of respondents with knowledge about prenatal exercise were aged 20–35 years, accounting for 19 individuals (63.4%), while the minority were aged over 35 years, totaling 3 individuals (10%). Based on education level, most respondents had completed high school (14 individuals or 46.6%), and the fewest had completed elementary school (3 individuals or 10%). Regarding occupation, the majority were housewives (17 individuals or 26.6%), and the minority were private employees (3 individuals or 3.3%). It is recommended that Alisah Clinic, Medan, use this scientific paper as a reference and input for midwifery practice, particularly in providing health education to pregnant women. Future researchers are advised to conduct broader studies with more comprehensive methods and variables to improve and refine this research.